Hukum Hibah ‘Umra menurut Imam Malik dan Kitab Undang-Undang Hukum Perdata Pasal 1666 - Ipah Saripah; Ila Nurmila (Fakultas Syari'ah | Institut Agama Islam Darussalam | IAID | Ciamis, Jawa Barat, Indonesia, 2019)
In the Shari'at Islam has taught its people to help each other in terms of virtue. The attitude of giving is a good deed, because helping can alleviate the economic pain of that person or another. With an attitude of giving or receiving someone's gift, a sense of unity and brotherhood will be created within the framework of religious harmony. This is manifested by the practice of a gift that helps someone who is in distress and gets the benefits of the item that has been donated. In this case the grant is ownership of the goods that have been granted (control of the goods) and can take advantage of the goods. The problem is whether or not it is permissible to withdraw an 'umra grant that has been given to someone, so that it will cause enmity and break the ties between them. Then how is the 'umra grant law' according to the Ulama, Imam Malik, and in the Civil Code Article 1666. It is used as a study by the author to carry out research and find out the purpose of the research. This study uses qualitative methods that produce descriptive data in the form of written or spoken words from people or observed behavior and this type of qualitative descriptive research uses a content analysis approach. The results of this research can be concluded as follows: general understanding of 'umra' that the return of 'umra after the person who is given dies is vanity. Therefore, with regard to the issue of 'umra, there will be permanent ownership for the person who is given' umra. Imam Malik is of the opinion that the 'umra grant is still valid, and the property returns to the owner of the property, but if the requirements are stated in the name of the offspring, then after the offspring is cut off the property will return to the owner of the property. The opinion of Imam Malik regarding the ability to do the'umra grant is based on the aspect of its benefits only and is qiyasyed like ariyah. And the most important thing in this case is the element of the benefits of the gift items and the first contract at the time of handing over the grant whether to mention for you and your children and grandchildren not What is needed is a witness so as not to cause fraud, to minimize any suspicions and disputes in the future. Based on Article 1666, in principle, a grant given by one person to another cannot be withdrawn or canceled, except in cases as regulated in Article 1688 of the Civil Law..